ANTIOXIDANT ACTIVITY OF ETHANOLIC EXTRACT AND FRACTION OF SALAK FRUIT SEEDS ( Salacca zalacca (Gaertn.) Voss. ) USING DPPH (2,2-diphenyl-1-picrylhydrazyl) METHOD - Sista Werdyani; Pinus Jumaryatno; Nur Khasanah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Salak seeds have been developed as a beverage, but there was still a little amount of research that focused on salak seeds. This research was conducted to find out the chemical compounds and the antioxidant activity of ethanolic extract and fraction of salak fruits seeds ( Salacca zalacca (Gaertn.) Voss. ) which have been grown extensively in Sleman Yogyakarta. Extraction was conducted using maceration, followed by fractionation using vacuum liquid chromatography. The identification of the chemical compounds contained in the ethanolic extract and fraction was performed by thin layer chromatography method, while the antioxidant activity was performed by DPPH method. Comparison of antioxidant activity was seen using IC50 values. The results showed that ethanol extract and fraction contained phenol, flavonoid, and tannin. The largest antioxidant activity was found in F7 with an IC50 value of 110.16 Î¼g / ml.